Determination of Capacities of Eccentric Stiffeners Part 1: Experimental Studies - Alvarez Rodilla, J.; Kowalkowski, Keith (Engineering Journal, 2021)
Forty column specimens were experimentally tested with an effort to identify the effective stiffener capacities of eccentric stiffeners when used within moment connections of beams connecting to column flanges. Three test methods were performed described as (1) single tension with load pulling away from the column specimen, (2) single compression with load applied toward the column specimen, and (3) double compression with load applied toward the column specimen and with a reaction plate directly opposite from the applied load. The sizes were selected with a range of slenderness ratios for the web and flange and to study multiple concentrated load limit states using AISC Specification Section J10 (AISC, 2016b). For each column size and test method, four column specimens were tested: (1) without stiffeners, (2) with stiffeners concentric with the applied load, (3) with stiffeners at a low eccentricity of 2 in. or 3 in., and (4) with stiffeners at a high eccentricity of 4 in. or 6 in. For column specimens tested without stiffeners and for compression tests, the maximum loads compared favorably to those predicted for web local crippling and were significantly higher than those predicted for web compression buckling (double compression tests) and web local yielding. For single tension tests, the maximum load always exceeded that predicted for the limit states of flange bending and web local yielding.